Question
Which is equivalent to \( (\sqrt[3]{125})^{x} \) ? \( 125^{\frac{1}{3} x} \) \( 125^{\frac{1}{3 x}} \) \( 125^{3 x} \) \( 1255^{\left[\frac{1}{3}\right)^{x}} \)
Ask by Gray Harper. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( 125^{\frac{1}{3} x} \)
Solution
The expression \( (\sqrt[3]{125})^{x} \) can be simplified step by step to find its equivalent form among the provided options.
1. **Simplify the Cube Root:**
\[
\sqrt[3]{125} = 5
\]
This is because \( 125 = 5^3 \).
2. **Raise to the Power of \( x \):**
\[
(\sqrt[3]{125})^{x} = 5^{x}
\]
Now, let's evaluate each of the given options to see which one matches \( 5^{x} \):
1. **Option 1: \( 125^{\frac{1}{3} x} \)**
\[
125^{\frac{1}{3} x} = (5^3)^{\frac{1}{3} x} = 5^{3 \cdot \frac{1}{3} x} = 5^{x}
\]
This matches exactly with \( (\sqrt[3]{125})^{x} \).
2. **Option 2: \( 125^{\frac{1}{3 x}} \)**
\[
125^{\frac{1}{3 x}} = (5^3)^{\frac{1}{3 x}} = 5^{\frac{3}{3 x}} = 5^{\frac{1}{x}}
\]
This does not match \( 5^{x} \).
3. **Option 3: \( 125^{3 x} \)**
\[
125^{3 x} = (5^3)^{3 x} = 5^{9 x}
\]
This does not match \( 5^{x} \).
4. **Option 4: \( 1255^{\left(\frac{1}{3}\right)^{x}} \)**
Assuming it's a typographical error and should be \( 125^{\left(\frac{1}{3}\right)^{x}} \):
\[
125^{\left(\frac{1}{3}\right)^{x}} = (5^3)^{\left(\frac{1}{3}\right)^{x}} = 5^{3 \left(\frac{1}{3}\right)^{x}}
\]
This does not match \( 5^{x} \).
**Conclusion:**
The equivalent expression to \( (\sqrt[3]{125})^{x} \) is:
**\( 125^{\frac{1}{3} x} \)**
**Answer:**
\( 125^{\frac{1}{3} x} \)
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Bonus Knowledge
To find the expression equivalent to \( (\sqrt[3]{125})^{x} \), we start by rewriting \( \sqrt[3]{125} \) in exponential form. We know that \( \sqrt[3]{125} = 125^{\frac{1}{3}} \). Thus, we can rewrite the original expression as: \[ (\sqrt[3]{125})^{x} = \left(125^{\frac{1}{3}}\right)^{x} \] Applying the power of a power property (which states that \( (a^{m})^{n} = a^{m \cdot n} \)), we have: \[ (125^{\frac{1}{3}})^{x} = 125^{\frac{1}{3} x} \] Therefore, the correct choice is: \( 125^{\frac{1}{3} x} \)